2013
DOI: 10.3109/0886022x.2013.773836
|View full text |Cite
|
Sign up to set email alerts
|

The Renal Endothelium in Diabetic Nephropathy

Abstract: Diabetic nephropathy is the leading cause of end-stage renal disease. Diabetes mellitus is characterized by generalized endothelial dysfunction. However, recent data also emphasizes the role of local renal endothelium dysfunction in the pathogenesis of diabetic nephropathy. Hyperglycemia triggers a complex network of signal-transduction molecules, transcription factors, and mediators that culminate in endothelial dysfunction. In the glomerulus, vascular endothelial growth factor-A (VEGF)-induced neoangiogenesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 120 publications
3
36
0
Order By: Relevance
“…However, in the late stage of DM, VEGF expression decreases, perhaps due to a decreased number of podocytes, resulting in fewer renal capillaries and a reduced GFR. Anti-VEGF therapy is effective in an early DKD model [29]. In the present study, we found that the serum VEGF level in the DKD patients (1.28±0.23 ng/ ml) was significantly higher than that in the DM patients without urinary protein excretion (0.94±0.21 ng/ml); additionally, VEGF was positively correlated with 24 h urinary protein, in agreement with the results of the above study.…”
Section: Discussionsupporting
confidence: 81%
“…However, in the late stage of DM, VEGF expression decreases, perhaps due to a decreased number of podocytes, resulting in fewer renal capillaries and a reduced GFR. Anti-VEGF therapy is effective in an early DKD model [29]. In the present study, we found that the serum VEGF level in the DKD patients (1.28±0.23 ng/ ml) was significantly higher than that in the DM patients without urinary protein excretion (0.94±0.21 ng/ml); additionally, VEGF was positively correlated with 24 h urinary protein, in agreement with the results of the above study.…”
Section: Discussionsupporting
confidence: 81%
“…[182][183][184][185] Interestingly, the treatment of diabetic mice with resveratrol, a well-known inducer of autophagy, protects from intraglomerular capillary rarefaction, suggesting that resveratrol attenuates DN by modulating angiogenesis. 186 Moreover, autophagy protects from high glucose-induced senescence in cord human venous endothelial cells.…”
Section: Autophagy In Aging and Diseased Kidneysmentioning
confidence: 97%
“…[2][3][4] Progressive and irreversible microvascular damage and loss are observed in the diabetic kidney, and a decrease in the function and density of intrarenal microvessels has been reported in several studies. [5][6][7][8] Furthermore, progressive podocyte injury, characterized by low microvessel density and number, hypertrophy, and foot process effacement, plays a central role in the development of DN in both type 1 and type 2 diabetes. 4,[9][10][11] Despite the crucial importance of the kidney, both as therapeutic target and as determinant of the prognosis of patients with DN, little is known about the mechanisms underlying kidney damage associated with diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…12,[24][25][26] Importantly, postmitotic podocytes exhibit high levels of basal autophagy as a key regulator of podocyte and glomerular maintenance. 13 Additionally, a strong body of evidence supports the role for maintenance of endothelial function in diabetes to limit DN progression involving homeostasis of multiple systems 7,[27][28][29][30] such as NOS3/eNOS (nitric oxide synthase 3 [endothelial cell]) activity, 31 glycocalyx production, 32,33 EDN/endothelin actions [34][35][36][37][38] and balanced VEGF (vascular endothelial growth factor) 33,39,40 and ANGPT/angiopoietin systems. 41 Endothelial cells may also use autophagy as a coping mechanism to metabolic stress.…”
Section: Introductionmentioning
confidence: 99%